Systematic variation of photoluminescence spectra with donor and acceptor concentrations ranging from 1 × 1010 to 1 × 1020 cm−3 in Si. (1st August 2022) - Tajima, Michio; Toyota, Hiroyuki; Ogura, Atsushi
Abstract: We review photoluminescence processes due to donor and acceptor impurities with concentrations ranging from 1 × 10 10 to 1 × 10 20 cm −3 in both uncompensated and compensated Si at 4.2 K for application to the impurity characterization. Systematic evolution and extinction were observed in the impurity bound exciton and impurity cluster bound exciton emission, donor-acceptor pair emission with and without discrete sharp lines, donor-band—to—acceptor-band emission, and the emission involving the intrinsic degenerate band. These variations occur as results of the transition from isolated impurity levels to interacting impurity levels due to impurity pairing or clustering in the concentration range around 1 × 10 16 cm −3, the formation of the impurity bands in the range mid 10 17 cm −3, and their unification with the intrinsic bands at critical Mott concentration of 3 × 10 18 cm −3 . Multiple radiative processes coexist in the transition regions and their intensities are determined by the impurity concentrations and the radiative probability of respective processes.